Differential effects of methotrexate and liposomally conjugated methotrexate in rat adjuvant-induced arthritis. - Williams, A S (1995)
In this study we evaluated the comparative efficacy of free and liposomally conjugated methotrexate on both disease induction and suppression of acute inflammation in rat adjuvant-induced arthritis. Rats were given either empty liposomes (E-LIPO), free methotrexate (MTX) or the liposomally conjugated methotrexate (MTX-LIPO) at a dose of 100 micrograms/day for 7 consecutive days by the intravenous route. When MTX treatment was initiated on the day of arthritis induction the drug suppressed but did not abolish the development of joint inflammation. Free MTX had no significant anti-inflammatory effect upon an established arthritis when dosing was commenced on day 11 post-adjuvant induction. Conversely, MTX-LIPO did not affect the progression of the arthritis when dosing was started on day 0, but exerted a significant anti-inflammatory effect on an established arthritis. MTX-LIPO treatment was significantly less haematotoxic than free MTX.